Hyperbaric oxygen therapy for local late radiation toxicity in breast cancer patients: A systematic review. (February 2023) - Meier, E.L.; Mink van der Molen, D.R.; Lansdorp, C.A.; Batenburg, M.C.T.; van der Leij, F.; Verkooijen, H.M.; Boonstra, O.; Hummelink, S.; Ulrich, D.J.O.
Abstract: Purpose: This systematic review aims to provide an overview of the literature on the effect of hyperbaric oxygen therapy (HBOT) on symptoms of local late radiation toxicity (LRT) in patients treated for breast cancer. Methods: A systematic search was performed in September 2021. All studies with a sample size of ≥10 patients reporting the effect of HBOT for symptoms of LRT after radiotherapy of the breast and/or chest wall were included. The ROBINS-I tool was used for critical appraisal of methodological quality. The toxicity outcomes pain, fibrosis, lymphedema, necrosis/skin problems, arm and shoulder mobility, and breast and arm symptoms were evaluated. Results: Nine studies concerning a total of 1308 patients were included in this review. Except for one study, sample sizes were small. Most studies had inadequate methodology with a substantial risk of bias. Post-HBOT, a significant reduction of pain was observed in 4/5 studies, of fibrosis in 1/2 studies, and of lymphedema of the breast and/or arm in 4/7 studies. Skin problems of the breast were significantly reduced in 1/2 studies, arm- and shoulder mobility significantly improved in 2/2 studies, and breast- and arm symptoms were significantly reduced in one study. Conclusion: This systematic review indicates that HBOT might be useful for reducing symptoms of LRT in breast cancer patients, however evidence is limited. A randomized controlled trial in a larger cohort of patients including a combination of patient- and clinician-reported outcome measures would be valuable to assess the effect of HBOT on symptoms of LRT. Highlights: Pain significantly reduced in four out of five studies. Fibrosis significantly reduced in one out of two studies. Lymphedema of the breast and arm significantly reduced in four out of seven studies. A randomized controlled trial is recommended for future research. A combination of patient- and clinician reported outcome measures would be valuable.